2010
DOI: 10.1111/j.1742-4658.2010.07700.x
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen synthase kinase 3β and β‐catenin pathway is involved in toll‐like receptor 4‐mediated NADPH oxidase 1 expression in macrophages

Abstract: Macrophage activation contributes to the pathogenesis of atherosclerosis. In the vascular system, the major source of reactive oxygen species is the NADPH oxidase (Nox) family. Nox1 is induced by lipopolysaccharide (LPS) in macrophages, but the expression mechanism is not fully understood. We found that LPS causes β‐catenin accumulation by glycogen synthase kinase 3β (GSK3β) inactivation, and that β‐catenin accumulation increases Nox1 expression. LPS induced Nox1 mRNA expression and reactive oxygen species gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 32 publications
(40 reference statements)
1
41
0
Order By: Relevance
“…This finding suggests that NOX1-derived production of ROS induced by 5-FU causes the upregulation of TNF-␣ in macrophages located in the lamina propria of intestinal mucosa, consequently triggering apoptotic mechanisms, including the activation of caspase-3 and caspase-8 in the intestinal crypt. While several studies have demonstrated that NOX1 is expressed in intestinal epithelial cells (18,42), expression of both NOX1 and NOX2 was recently observed in the murine monocyte/macrophage cell line RAW264.7 (11,20). Interestingly, we also detected NOX1 mRNA expression in isolated peritoneal macrophages, and this expression was upregulated by lipopolysaccharide (data not shown), suggesting a possibility that NOX1 expressed in inflammatory cells may be involved in the pathogenesis of intestinal mucositis.…”
Section: Discussionsupporting
confidence: 55%
“…This finding suggests that NOX1-derived production of ROS induced by 5-FU causes the upregulation of TNF-␣ in macrophages located in the lamina propria of intestinal mucosa, consequently triggering apoptotic mechanisms, including the activation of caspase-3 and caspase-8 in the intestinal crypt. While several studies have demonstrated that NOX1 is expressed in intestinal epithelial cells (18,42), expression of both NOX1 and NOX2 was recently observed in the murine monocyte/macrophage cell line RAW264.7 (11,20). Interestingly, we also detected NOX1 mRNA expression in isolated peritoneal macrophages, and this expression was upregulated by lipopolysaccharide (data not shown), suggesting a possibility that NOX1 expressed in inflammatory cells may be involved in the pathogenesis of intestinal mucositis.…”
Section: Discussionsupporting
confidence: 55%
“…19,21 We have now shown that Nox expression and ROS generation are increased by LPS in peritoneal macrophages. Whereas the basal level of Nox2 was relatively high, that of Nox1 was low and Nox4 was undetectable.…”
Section: Nox1-ros Signaling Functions Downstream Of Blt2 In Lpsinducementioning
confidence: 99%
“…[16][17][18] ROS generation has also been found to be important for LPS signaling in macrophages, and LPS-induced ROS generation in these cells is attenuated by DPI, an inhibitor of flavoenzymes, including Nox. [19][20][21] We therefore investigated whether BLT2-dependent, Nox-mediated ROS generation might contribute to LPS-induced IL-6 synthesis in mouse peritoneal macrophages. First, consistent with previous observations, we found that LPS induced ROS production in a manner sensitive to DPI or NAC, a free radical scavenger, in peritoneal macrophages (Figure 4a).…”
Section: Nox1-ros Signaling Functions Downstream Of Blt2 In Lpsinducementioning
confidence: 99%
“…This pathway plays an essential role in inflammation and immune cells. 17,18 In particular, many groups have shown that GSK3b, through TLR signaling, is necessary for inflammation. For example, GSK3b regulates TLR-mediated cytokine production, and inactivation of GSK3b by LPS has a negative effect on production of the proinflammatory cytokine interferon-b.…”
Section: Introduction Rmentioning
confidence: 99%
“…Akt is a typical protein that directly phosphorylates and inactivates GSK3b. 18 We have previously investigated the importance of Akt as an inflammation mediator. Although the importance of Akt was studied for the TLR4-induced inflammatory response, the Akt pathway inhibitor LY294002 also inhibited HKLM-induced inflammation (data not shown).…”
mentioning
confidence: 99%